2011
DOI: 10.1074/jbc.m110.196345
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Modulation of the Epstein-Barr Virus-induced Seven-transmembrane Receptor EBI2

Abstract: The Epstein-Barr virus-induced receptor 2 (EBI2) is a constitutively active seven-transmembrane receptor, which was recently shown to orchestrate the positioning of B cells in the follicle. To date, no ligands, endogenously or synthetic, have been identified that modulate EBI2 activity. Here we describe an inverse agonist, GSK682753A, which selectively inhibited the constitutive activity of EBI2 with high potency and efficacy. In cAMP-response element-binding protein-based reporter and guanosine 5-3-O-(thio)-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 46 publications
5
75
0
Order By: Relevance
“…As a result, these cells are less strongly attracted to the B-T zone interface and relocate to the outer follicle in an EBI2-dependent manner. A recent study suggested EBI2 transmits pro-proliferative signals to B cells (Benned-Jensen et al, 2011). We have not found 7α,25-OHC to have mitogenic effects on B cells (T.Y., L.M.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these cells are less strongly attracted to the B-T zone interface and relocate to the outer follicle in an EBI2-dependent manner. A recent study suggested EBI2 transmits pro-proliferative signals to B cells (Benned-Jensen et al, 2011). We have not found 7α,25-OHC to have mitogenic effects on B cells (T.Y., L.M.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of EBI2 leads to adenylate cyclase inhibition and subsequent reduction of cAMP production. EBI2 also was reported to activate extracellular signal-regulated kinase (Benned-Jensen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous structure-function studies with EBI2 were focused largely on investigating its constitutive activity. Those studies revealed important structural motifs for the ligand-independent activity of the receptor and suggested potential molecular constraints during receptor transition from the inactive conformation to the active conformation (Benned-Jensen and Rosenkilde, 2008;Benned-Jensen et al, 2011). We decided to explore the molecular mechanisms of ligand-dependent activation of EBI2 by using 7␣,25-OHC as a tool.…”
Section: Introductionmentioning
confidence: 99%
“…B cells with EBI2 knocked out exhibit defective migration, resulting in strongly impaired T-cell-dependent antibody responses. Selective EBI2 antagonists, such as ML401 which has a central piperazine core, have been reported [10], and also a spirocyclic inverse agonist (GSK682753 from GlaxoSmithKline, Brentford, UK) [11] on which the compounds of this invention have been modeled, probably aiming at increasing the metabolic stability beyond that of GSK682753. Biological data are all but absent, although a cell-based luminescent assay is stated to have shown IC 50 values 'below 100 nM' for many of the compounds that were chemically identified in detail.…”
mentioning
confidence: 99%